Quantification of mRNA expression by competitive PCR using non-homologous competitors containing a shifted restriction site - Watzinger, Franz (Oxford University Press, 2001)
Despite the recent introduction of real-time PCR methods, competitive PCR techniques continue to play an important role in nucleic acid quantification because of the significantly lower cost of equipment and consumables. Here we describe a shifted restriction-site competitive PCR (SRS-cPCR) assay based on a modified type of competitor. The competitor fragments are designed to contain a recognition site for a restriction endonuclease that is also present in the target sequence to be quantified, but in a different position. Upon completion of the PCR, the amplicons are digested in the same tube with a single restriction enzyme, without the need to purify PCR products. The generated competitor- and target-specific restriction fragments display different sizes, and can be readily separated by electrophoresis and quantified by image analysis. Suboptimal digestion affects competitor- and target-derived amplicons to the same extent, thus eliminating the problem of incorrect quantification as a result of incomplete digestion of PCR products. We have established optimized conditions for a panel of 20 common restriction endonucleases permitting efficient digestion in PCR buffer. It is possible, therefore, to find a suitable restriction site for competitive PCR in virtually any sequence of interest. The assay presented is inexpensive, widely applicable, and permits reliable and accurate quantification of nucleic acid targets.